1984
DOI: 10.1111/j.1600-0528.1984.tb01433.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the relationship between deviations in X‐ray angulation and images of proximal overlapping on bite‐wing radiographs

Abstract: Eleven child skulls were radiographed through a range of 50 degrees by varying the horizontal angulation of the X-ray beam in steps of 2 or 5 degrees. The changes in the width of overlapping contact images and the ranges through which no overlap occurred were measured. A linear relationship between changes in X-ray beam angulation and overlap width was found in all the skulls. Using the data it was calculated that for each increase in overlap width of 0.1 mm, 95% of the deviations in X-ray beam angulation were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…Admittedly coarse when compared to progression/reversal measurements based on radiographic findings, the epidemiologic indices utilized in the present study offered a straightforward array of clear-cut stages. Furthermore, our conclusions are not open to the reliability questions that radiographic artifacts (mainly the reproducible repositioning of beam angulations) create in smaller study designs based on radiographic records to ascertain progression (reversal) of lesions [Pitts, 1983b;McDonald, 1984;Benn and Watson, 1989;Van der Stelt et al, 1989]. Despite its solid design, the investigation may have suffered from certain shortcomings.…”
Section: Discussionmentioning
confidence: 99%
“…Admittedly coarse when compared to progression/reversal measurements based on radiographic findings, the epidemiologic indices utilized in the present study offered a straightforward array of clear-cut stages. Furthermore, our conclusions are not open to the reliability questions that radiographic artifacts (mainly the reproducible repositioning of beam angulations) create in smaller study designs based on radiographic records to ascertain progression (reversal) of lesions [Pitts, 1983b;McDonald, 1984;Benn and Watson, 1989;Van der Stelt et al, 1989]. Despite its solid design, the investigation may have suffered from certain shortcomings.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, caries detection may be hampered by poor technique and unequally trained operators. [2][3][4] Adding to the challenge of correctly exposing SBWs, a systematic review of the literature by Bader et al reported that the median sensitivity value for proximal caries was 49%. 5 One of the primary goals of SBW radiographic technique is to open the proximal contacts so that no superimposition of the tooth surfaces occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Both standardized and nonstandardized techniques have been employed. Many authors have emphasized the importance of standardized teehniques and correct angulations in radiographie diagnoses (1_3), SEWERIN (4) and LEIJON (5) have obtained different earies scores simply by changing the horizontal angulation of the X-ray beam, LEIJON concluded that a carious lesion tnay appear as an enamel lesion in one projection and a dentin lesion in another, MCDONALD (6) demonstrated an increase in overlap of 0,1 mm by varying the X-ray beam by less than 2,5° in the horizontal direetion. Referring to his own study and a study made by HOROWITZ (7), he suggested that "the positioning of the X-ray beam so as to cause no overlapping was at best difficult and at worst impossible," SEW- ERIN (8) reported up to 80% overlapping, indicating that overlapping may be a great clinical problem.…”
mentioning
confidence: 99%